Marrow damage and hematopoietic recovery following allogeneic bone marrow transplantation for acute leukemias: Effect of radiation dose and conditioning regimen. Issue 1 (January 2016) - Wilke, Christopher; Holtan, Shernan G.; Sharkey, Leslie; DeFor, Todd; Arora, Mukta; Premakanthan, Priya; Yohe, Sophia; Vagge, Stefano; Zhou, Daohong; Holter Chakrabarty, Jennifer L.; Mahe, Marc; Corvo, Renzo; et al.
Abstract: Background and purpose: Total body irradiation (TBI) is a common component of hematopoietic cell transplantation (HCT) conditioning regimens. Preclinical studies suggest prolonged bone marrow (BM) injury after TBI could contribute to impaired engraftment and poor hematopoietic function. Materials and methods: We studied the longitudinal changes in the marrow environment in patients receiving allogeneic HCT with myeloablative (MA, n = 42) and reduced intensity (RIC, n = 56) doses of TBI from 2003–2013, including BM cellularity, histologic features of injury and repair, hematologic and immunologic recovery. Results: Following MA conditioning, a 30% decrease in the marrow cellularity persisted at 1 year post-transplant ( p = 0.03). RIC HCT marrow cellularity transiently decreased but returned to baseline by 6 months even though the RIC group received mostly umbilical cord blood (UCB) grafts (82%, vs. 17% in the MA cohort, p < 0.01). There was no evidence of persistent marrow vascular damage or inflammation. Recipients of more intensive conditioning did not show more persistent cytopenias with the exception of a tendency for minimal thrombocytopenia. Immune recovery was similar between MA and RIC. Conclusions: These findings suggest that TBI associated with MA conditioning leads to prolonged reductions in marrow cellularity, but does not show additional histological evidence of long-term injury, which is further supported by similar peripheral counts and immunologic recovery.